Steep HIV prevalence declines among young people in selected Zambian communities: population-based observations (1995-2003) - Dzekedzeke Kumbutso; Sandøy Ingvild F; Michelo Charles; Siziya Seter; Fylkesnes Knut (BMC, 2006)
Abstract Background Understanding the epidemiological HIV context is critical in building effective setting-specific preventive strategies. We examined HIV prevalence patterns in selected communities of men and women aged 15-59 years in Zambia. Methods Population-based HIV surveys in 1995 (n = 3158), 1999 (n = 3731) and 2003 (n = 4751) were conducted in selected communities using probability proportional to size stratified random-cluster sampling. Multivariate logistic regression and trend analyses were stratified by residence, sex and age group. Absence, <30% in men and <15% in women in all rounds, was the most important cause of non-response. Saliva was used for HIV testing, and refusal was <10%. Results Among rural groups aged 15-24 years, prevalence declined by 59.2% (15.7% to 6.4%, P < 0.001) in females and by 44.6% (5.6% to 3.1%, P < 0.001) in males. In age-group 15-49 years, declines were less than 25%. In the urban groups aged 15-24, prevalence declined by 47% (23.4% to 12.4%, P < 0.001) among females and 57.3% (7.5% to 3.2%, P = 0.001) among males but were 32% and 27% in men and women aged 15-49, respectively. Higher educated young people in 2003 had lower odds of infection than in 1995 in both urban [men: AOR 0.29(95%CI 0.14-0.60); women: AOR 0.38(95%CI 0.19-0.79)] and rural groups [men: AOR 0.16(95%CI 0.11-0.25), women: AOR 0.10(95%CI 0.01-7.34)]. Although higher mobility was associated with increased likelihood of infection in men overall, AOR, 1.71(95%CI 1.34-2.19), prevalence declined in mobile groups also (OR 0.52 95%CI 0.31-0.88). In parallel, urban young people with ≥11 school years were more likely to use condoms during the last casual sex (OR 2.96 95%CI 1.93-4.52) and report less number of casual sexual partners (AOR 0.33 95%CI 0.19-0.56) in the last twelve months than lower educated groups. Conclusion Steep HIV prevalence declines in young people, suggesting continuing declining incidence, were masked by modest overall declines. The concentration of declines in higher educated groups suggests a plausible association with behavioural change.